ELEVATED TROPONIN OF NON-CORONARY ETIOLOGY A REVIEW - Flavio Gomes Jardim Filho, Marcelo (Health and Society, 2024)
Elevated troponin levels are traditionally associated with acute myocardial infarction (AMI) and are widely used as a specific marker for the diagnosis of ischemic myocardial injury. However, recent studies have shown that elevated troponin levels can occur in several non-coronary conditions, requiring a more careful diagnostic approach to avoid misinterpretations and inadequate management. This study aimed to perform a systematic review of the literature on the non-coronary causes of elevated troponin levels, seeking to identify the main associated clinical conditions and discuss their prognostic value in different contexts. To this end, a systematic review of articles published between 2014 and 2024 was conducted using the PubMed, Scopus and Web of Science databases. The results revealed that conditions such as sepsis, pulmonary embolism (PE), chronic renal failure (CRF), chronic obstructive pulmonary disease (COPD) and tachyarrhythmias are the main non-coronary causes of elevated troponin levels. It is concluded that elevated troponin levels of non-coronary etiology are an important marker of severity and poor prognosis in several systemic conditions. Troponin levels should be interpreted carefully, taking into account the clinical context and underlying conditions of each patient.